Study on the emotional stress of students of the Kolej Canselor (KC), Universiti Putra Malaysia during the Movement Control Order (MCO) of Pandemic Covid-19 - Abdullah, Amini Amir; Awang, Mohd. Daud (Human Resource Management Academic Research Society, 2021)
This study is about the campus life of Kolej Canselor (KC) students, Universiti Putra Malaysia (UPM) during the Movement Control Order (MCO) from 18 March 2020 to 14 April 2020. The aspects examined are the value of patience, level of mental, emotional and psychosocial well-being among KC students during the period of the Covid-19 Movement Control Order (MCO). This study aims to identify the social support and diversity approach needed by students during the MCO. This research used quantitative method to obtain data when the Covid-19 pandemic is at an alarming level. The study involved 136 KC students staying at the Kolej Canselor residential college, UPM and found that 24.3% of students felt depressed during the period. A total of 13.7% of respondents stated that their level of depression was high compared to low and interestingly, 47.8% stated that they would like to return to their hometown if allowed. The students experienced something new during the MCO which they had never felt before. The KC management has provided various assistance services to the students while the Student Affairs Division has provided support services such as counseling services to help the psychological impact of the students during the MCO period.